A new gypsophilous species of Chaenorhinum (Antirrhinaceae) from the south-east of the Iberian Peninsula. (2nd January 2016) - Güemes, J.; Marchal, F.; Carrió, E.; Blasco, M. P.
Abstract : A new strict gypsophilous species of Chaenorhinum, Ch. gamezii, is described. It is an annual to perennial species found in extremely arid locations upon Triassic gypsic habitats in the south-eastern Iberian Peninsula. This species has an eglandular heterotrichous indumentum, which is related to Ch. segoviense and Ch. flexuosum . However, Ch. gamezii has a characteristic combination of vegetative and micromorphological features (trichomes and ornamentation of the seeds) that are not present in any other taxon of the genus. Herein, the affinities and differences with related species are studied and discussed. For its differentiation, an original key is presented with comparative figures of indumentum and seeds, and a complete iconography. Knowledge of the species ecology, biogeography, demography and threats is also provided, and according to that, Ch. gamezii should be considered as a critically threatened species (critically endangered, according to IUCN criteria). Future conservation proposals are discussed.